2018
DOI: 10.1126/science.aar4777
|View full text |Cite
|
Sign up to set email alerts
|

The periodic coloration in birds forms through a prepattern of somite origin

Abstract: The periodic stripes and spots that often adorn animals’ coats have been largely viewed as self-organizing patterns, forming through dynamics such as Turing’s reaction-diffusion within the developing skin. Whether preexisting positional information also contributes to the periodicity and orientation of these patterns has, however, remained unclear. We used natural variation in colored stripes of juvenile galliform birds to show that stripes form in a two-step process. Autonomous signaling from the somite sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 21 publications
7
68
0
1
Order By: Relevance
“…Such combinatorial patterning modules can therefore contribute to increase pattering robustness as well as boost the potential for their evolutionary reshuffling. 33,36,37 Hence, it appears that the strict dichotomy often attributed to the deployment of these two distinct patterning concepts during embryogenesisthat is, "positional information" or "self-organization"is likely artificial and, as previously suggested, a more realistic approximation of development would entail various combinations of the two ( Figure 1B,C). 8,18,19 3 | ARTHROPOD…”
Section: The Formation Of Repetitive Patterns In Nature-positional mentioning
confidence: 68%
See 1 more Smart Citation
“…Such combinatorial patterning modules can therefore contribute to increase pattering robustness as well as boost the potential for their evolutionary reshuffling. 33,36,37 Hence, it appears that the strict dichotomy often attributed to the deployment of these two distinct patterning concepts during embryogenesisthat is, "positional information" or "self-organization"is likely artificial and, as previously suggested, a more realistic approximation of development would entail various combinations of the two ( Figure 1B,C). 8,18,19 3 | ARTHROPOD…”
Section: The Formation Of Repetitive Patterns In Nature-positional mentioning
confidence: 68%
“…Collectively, combining “positional information” with growth and additional patterning modules alleviates many of the problems inherent to the establishment of highly repetitive structures, were they to be specified by “positional information” only (eg, setting up reliable long‐range gradients or precisely defining multiple threshold values). Such combinatorial patterning modules can therefore contribute to increase pattering robustness as well as boost the potential for their evolutionary reshuffling . Hence, it appears that the strict dichotomy often attributed to the deployment of these two distinct patterning concepts during embryogenesis—that is, “positional information” or “self‐organization”—is likely artificial and, as previously suggested, a more realistic approximation of development would entail various combinations of the two (Figure B,C) …”
Section: The Formation Of Repetitive Patterns In Nature—positional Inmentioning
confidence: 84%
“…The chicken Gallus gallus historically served as model: consistent with previous work 7 we observed that when completed (at E11) its dorsal tract covers ~77% of the skin surface and displays an orderly arrangement in which adjacent longitudinal rows (i.e., feather rows; fr) contain a reproducible number of feather follicles (F=25 as quantified between wings and tail in medial rows) and form "chevrons" along the dorso-ventral axis. For comparison, we chose two close relatives in the Galliform bird group, namely the Japanese quail Coturnix japonica and the common pheasant Phasianus colchicus in which we previously described feather distribution 17 . In Galliforms, overall tract size (~75 and 72% of dorsum surface, respectively), shape, and geometry are conserved, while the number of feathers per row is species-specific: F=17 in the quail (except in fr#1 known to develop later where F=10 17 ) and F=23 in the pheasant.…”
Section: Resultsmentioning
confidence: 99%
“…After egg incubation in Brinsea Ovaeasy 190 incubators, embryos were treated in ovo with 9mg/mL of 5-Bromo-2′-deoxyuridine solution (Sigma; BrdU incorporation experiments), and dissected. Flat skins were prepared as described previously 17 . Specimens were fixed in 4% formaldehyde, and imaged.…”
Section: Embryo Sampling and Flat Skin Preparationmentioning
confidence: 99%
See 1 more Smart Citation